Investigations of multi-carrier pulse width modulation schemes for diode free neutral point clamped multilevel inverters - Chokkalingam B.; Bhaskar M.S.; Padmanaban S.; Ramachandaramurthy V.K.; Iqbal A. (Korean Institute of Power Electronics, 2023)
Balancing; Diodes; Field programmable gate arrays (FPGA); Harmonic distortion; Induction motors; Pulse width modulation; Voltage control; Wave filters; 3-level inverters; Multi carrier pulse width modulation; Multilevel inverter; Total harmonic distortion (THD); Xilinx system generator; Electric inverters